IMPLEMENTASI KEBIJAKAN ELEKTRONIK KARTU TANDA PENDUDUK (E-KTP) DI KABUPATEN KUANTAN SINGINGI - Zulkifli Zulkifli; Made Devi Wedayanti; Nita Arjuna (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2019)
The implementation of the national electronic program for current residents' cards and future time frames has always been an actual phenomenon to be discussed and researched. The same phenomenon in linear terms certainly reaches throughout the regency and city areas in Indonesia, including in KuantanSingingi Regency. The purpose of this study was to find out and analyze the conditions of the objective implementation of the resident card electronic policy in KuantanSingingi Regency. The reference analysis is an indicator of the implementation of public policy theory - communication, resources, disposition, bureaucratic structure. The research method used descriptive survey, data analysis instruments using frequency tables. Sunber frequency table data from Likert scale development. Likert scale is used as a reference to categorize the opinions or attitudes of respondents. While the main instrument for collecting data is a semi-guided interview. The results of the study, the implementation of the electronic policy of identity cards in KuantanSingingi District has been well run by the implementors